ANALYSING THE BARRIERS FOR IMPLEMENTING AN EFFECTIVE SUPPLY CHAIN FOR THE PUBLIC DISTRIBUTION SYSTEM IN INDIA: A TISM APPROACH - Bohtan, Ajay; Mathiyazhagan, Dr. Kaliyan; Vrat, Prof. Prem (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The National Food Security Act-2013 (NFSA) in India has the primary aim of ensuring food security in India. This has to be achieved through the existing Public Distribution System (PDS). The foodgrains undergo a vast supply chain wherein after procurement from the farmers these are transported and stored at various levels before being finally distributed to the intended beneficiaries. It has been seen that this long and complex supply chain is not effective due to various obstacles and barriers in its efficient implementation. This paper analyses the barriers which impede the implementation of an effective Supply Chain Management (SCM) in PDS using Total Interpretive Structural Modeling (TISM). The work has been divided into two main phases one being the identification of fifteen barriers and the other being their qualitative analysis. Initially the Interpretive Structural Modeling (ISM) qualitative analysis was used to understand the mutual influences amongst the barriers by survey/questionnaire. This part identified the dominant barriers which prevent the adoption of an effective supply chain management. Later the TISM approach was used to bring out the exact influence of the barriers on each other. The result of this study would be helpful for the government to adopt an efficient PDS supply chain thereby reducing the ever increasing burden of subsidy. Implementation of an effective PDS supply chain would also help in achieving the aim of NFSA in the most efficient way.